(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In today’s world, data security is very important. In the area of information and communication technology, security has become a major issue. Steganography is used for highly secure, secret information exchange.To design a digital data security application, we proposed combining the cryptography technique with the DES technique and the steganographytechnique with the DCT. The approachmay be utilized to protect data in pdf files, PowerPoint, Excel or Word. Data is encrypted using the DES method and then concealed using the DCT method in the image. The outcomes show that the trait of the incorporated image (stego-image) is still good, having a PSNR value of 48.9 dB on average. In fact, the results of the experiment show an average computational time of 0.77 millisecond/byteand an average dimensionincrement of 4.29 times, and a 60 percent accomplishment rate. This work may aid in resolving the situation of data confidentiality when transmitted via a wide network such as the internet.